Labors of imagination : aesthetics and political economy from Kant to Althusser - Mieszkowski, Jan, 1968- (Fordham University Press, 2006)
Challenging various assumptions about the relationship between language and politics, this book offers an account of aesthetic and economic thought since the eighteenth century. Providing a contribution to contemporary debates about culture and ideology, it is suitable for scholars of literature, history, and political theory.